Guided Inquiry Based Teaching Module to Improve Students’ Learning Outcomes and Curiosity: A Literature Review - Pioka Anggara; Tri Ariani (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2025)
Physics learning in schools often remains dominated by conventional, teacher-centered approaches, limiting students’ opportunities to explore concepts and develop curiosity. This condition contributes to low learning outcomes and weak conceptual understanding. This study aims to analyze how guided inquiry-based learning modules can improve students’ curiosity and learning outcomes. The method used was a literature review by examining 50 Sinta 2-5 indexed articles published between 2017 and 2025. Then, 10 of the most relevant articles were selected for in-depth analysis. The results of the study indicate that the steps of inquiry observing, asking, formulating hypotheses, exploring, and concluding consistently foster students’ curiosity and increase their engagement in the learning process. In addition, all articles reported significant improvements in learning outcomes, demonstrated by increases in grades, conceptual understanding, and moderate to high n-gain. In conclusion, inquiry-based learning modules are valid, practical, and highly effective teaching materials in improving students’ curiosity and learning outcomes.